Digitalization of control and supervision activities: Russian and French experience - Elena V. Gritsenko; Pavel A. Kuryndin (Правоприменение, 2020)
The subject of the article is legal regulation at the transition stage from e-government to digital government in Russia and France.The purpose of the article is confirmation or confutation of the hypothesis that in the practice of digital interaction between administrative bodies and individuals, there are problems that must be clearly identified and can be solved using the French experience of legal regulation of the digitalization of public administration.The methodology of the study includes comparative analysis, description as well as particular academic legal methods (interpretation of legal acts, judicial acts and state programs of digitalization in Russia and France, formal legal method).The main results and scope of their application. Russia and France are similar because of not only belonging to the continental legal system, but also existing in the transition stage from e-government to digital. Public administration and law in both countries have to cope with the challenges of digitalization. In this regard, the experience of implementing reforms in France, which is known for its administrative and legal traditions and successes, is of particular interest to the Russian Federation. The legal support of public administration digitalization is clearly lagging behind the rapid development of digital technologies; moreover, new information solutions are significantly ahead of their legal implementation. A comparative analysis between the strategic plans of public administration, relating to digitalization of control and supervision activities in the Russian federation, and the e-government's present and future legislative framework, indicates a lack of coherence between the plans and their legislative counterparts. The initial implementation of public administration digitalization strategic plan through legislation on services is generally supported in the “Digital Public Administration” federal project through the legislation of services. At the same time, the draft of the new Federal law on state control (supervision) and municipal control in Russia offers its own information infrastructure for control and supervisory activities.Conclusions. In order to overcome the fragmentation in the regulation of electronic interaction between private entities and public administration, the French experience of regulating the general principles of administrative procedures and guarantees of good public administration in a single act is very useful. Such an approach would also ensure compliance with the basic principles of proportionality and the prohibition of excessive formalism in the meaningful differentiation of errors and violations committed in the course of electronic communication. In addition according to French experience, it is necessary to maintain alternative ways of communication with administrative authorities including electronic ones, and consider any legislative exceptions. Also, it is necessary to define additional guarantees to citizens during interactions with technical support services; defining standards for the legal qualification of technical failures, pre-trial and judicial appeal mechanisms against automatically made decisions.